PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATERI TUJUAN DAN FUNGSI AL-QUR’AN DI MAN 3 PARIGI - Latif, Muhamad (LP2M STAI Darul Kamal NW Kembang Kerang, 2021)
Abstract This study discusses the application of the Discovery Learning Model to Improve Student Learning Outcomes on the Objectives and Functions of the Qur'an at MAN 3 Parigi. The objectives of this research are: to find out the learning outcomes of students in class X MIA IA in the subjects of the Qur'an Hadith before using the discovery learning model and how the learning outcomes of students in class X MIA IA in the subjects of the Qur'an Hadith after using the discovery learning model, is there any effect of the discovery learning model on the learning outcomes of class X MIA IA students in the subjects of al-Qur'an Hadith. Learning with the Application of the Discovery Learning Method has a positive impact on improving student learning achievement which is marked by an increase in student learning mastery in each cycle, namely cycle I (70.00 %), cycle II (86.00 %). Thus the Discovery Learning Model can improve student learning outcomes in class X MIA 1A MAN 3 Parigi.